2015
DOI: 10.17507/jltr.0701.04
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behavior and Chinese ESL Students’ In-class Participation

Abstract: Abstract-Chinese demand for American-style education is on the rise as many Chinese students seek opportunities to gain a true global education in China. However, importing US education style in China is challenging. American education emphasizes the importance of students' in-class participation; however, Chinese students' reluctance to communicate in class is notoriously strong. To explain such reluctance, scholars have focused their attention on constructs such as "willingness to communicate" and "communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It revealed that the students' attitudes concerning m-learning, subjective norm, and behavioural control influenced their intention to adopt m-learning, inferring that the adoption needs should be regarded from different perspectives. Another study on Chinese ESL students' in-class participation revealed that the stronger predictors for students' participation were attitudes toward participation and self-efficacy, and female students had stronger intentions to participate in class (Girardelli & Patel, 2015). TPB framework was also applied in research to teacher's intentions and behaviour in the classroom (Lee et al 2010).…”
Section: Behavioural Intentionmentioning
confidence: 99%
“…It revealed that the students' attitudes concerning m-learning, subjective norm, and behavioural control influenced their intention to adopt m-learning, inferring that the adoption needs should be regarded from different perspectives. Another study on Chinese ESL students' in-class participation revealed that the stronger predictors for students' participation were attitudes toward participation and self-efficacy, and female students had stronger intentions to participate in class (Girardelli & Patel, 2015). TPB framework was also applied in research to teacher's intentions and behaviour in the classroom (Lee et al 2010).…”
Section: Behavioural Intentionmentioning
confidence: 99%
“…Almost all professors would like greater oral participation—especially in large lecture classes. The numerous articles and studies concerned with increasing participation are self‐evident examples of this concern (Banks, 2008; Fredricks, Blumenfeld, & Paris, 2004; Girardelli & Patel, 2015; Hurt, Scott, & McCroskey, 1978; O’Connor, 2013; Rocca, 2010). Why do professors want more participation?…”
Section: Introductionmentioning
confidence: 99%
“…Participation also prepares students for leadership and collaborative work in professional careers. Being able to discuss, analyze, argue, and respond in a workforce setting is a key skill for professional success (Girardelli & Patel, 2015). “No matter how it is defined, there is strong evidence for the importance of participating in class” (Rocca, 2009, p. 22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, introducing American-style educational practices in China is in many ways challenging: Chinese students tend to be unwilling to communicate orally in class. This reticence is particularly problematic in activities that target students' speaking skills (Girardelli & Patel, 2016).…”
Section: Introductionmentioning
confidence: 99%